MORPHOLOGICAL CHARACTERISTIC OF RENAL CORPUSCLES IN RATS AFTER ADMINISTERING CRYOPRESERVED PLACENTA - Kapustyanska, A.A. (World of Medicine and Biology, 2018)
The previously obtained positive experimental and clinical data on the use of cryopreserved placenta administration in the treatment of many diseases and the lack of sufficient scientific research in the field of inflammatory processes correction in the kidneys by this method prompted us to carry out this work. The purpose of this work is to study the morphological features of renal corpuscles in rats under the conditions of cryopreserved placenta administration. The study was carried out on 14 rats of the Wistar line. The first group consisted of 5 intact animals, the second group consisted of 9 animals, who were injected subcutaneously with a cryopreserved placenta. The microscopic studies of the white rats’ kidney cortical substance under the conditions of cryopreserved placenta showed that the most significant changes take place within the 1st-7th days of the experiment. On the 10 - 14th day of the experiment, the structural organization of the renal corpuscles adapted to the kidneys of intact animals is restored.
Keywords: kidney; renal corpuscle; rats; cryopreserved placenta